Pengaruh Digital Marketing, Celebrity Endorsement Dan Kualitas Produk Terhadap Minat Beli Deliwafa Store Malang Studi Kasus Pada Mahasiswa FEB Universitas Islam Malang Angkatan 2020 - Laysia, Teressa Wiga; Nurhidayah, Nurhidayah; Amin, Muhammad Sirojuddin (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The purpose of this study was to explain digital marketing, celebrity endorsement, product quality and purchase intention and to find out digital marketing, celebrity endorsement and product quality on buying interest partially. The research method used is quantitative research method and this type of research is purposive sampling. The sample of this research is active students of S1 FEB Islamic University Malang with a total of 85 respondents. To obtain data, this study used a data collection method with a questionnaire. The data analysis used is instrument test, normality test, classical assumptions, multiple linear regression analysis, hypothesis testing, and the coefficient of determination using the SPSS 23 application. The results of this study indicate that digital marketing, celebrity endorsement and product quality have a partial effect on buying interest in Deliwafa Store Malang. Keywords: Digital Marketing, Celebrity Endorsement, Product Quality And Purchase Intention